Design and Development of an Autonomous Underwater Vehicle (AUV-FKEUTeM) - Mohd Aras, Mohd Shahrieel; Kasdirin, Hyreil Anuar; Jamaluddin, Muhamed Herman; Basar, Mohd Farriz (2009)
Abstract—This paper describes a design and development of an Autonomous Underwater Vehicle (AUV). AUV are robotic submarines that are a part of the emerging field of autonomous and unmanned vehicles. This project shows the design implementation of an AUV as a test bed platform for a variety of research in underwater technologies especially involving small-scale, surface water and low-cost underwater robots. The general design and its consideration are well discussed in this paper. The AUV prototype has been developed by SolidWork. It will have a fixed mechanical system and body, having a modular electronic system that allows development of various controllers. The controller and motors has been tested in small scale surface water and the result is encouraging. Some of the factor affecting the AUV performance is also elaborated for future research in this area.